EFEKTIVITAS STRATEGI GURU MENGATASI MASALAH ATTENTION GETTING BEHAVIOR SISWA MENGGUNAKAN PERUBAHAN PERILAKU DI SDIT BINA MULIA: EFEKTIVITAS STRATEGI GURU MENGATASI MASALAH ATTENTION GETTING BEHAVIOR SISWA MENGGUNAKAN PERUBAHAN PERILAKU DI SDIT BINA MULIA - Ade Husnaeni; Siskha Putri; Aradelia Pikkan Wahyudi ‎; Abdul Latif (Journal of Education and Culture (JEC), 2023)
This research basically aims to be able to find out about the effectiveness of the teacher's strategy to overcome the problem of attention getting behavior of students using behavior change. This research used a type of qualitative research. Data collection is done by interviews, observation, and documentation. The results of this research also show that in the teacher's strategy to overcome the problem of attention getting behavior, namely: 1) the effectiveness of the teacher in implementing geeting behavior to students. 2) Changes in student behavior. It can be concluded based on research results, education can be carried out properly, teachers can carry out learning innovations that involve all parties between teachers and schools, teachers and students, and teachers and parents. The involvement of various parties in the educational process will result in diversity, collectivity, variation and selection in the interactions between actors involved in the educational process.